PENGARUH PENGEMBANGAN KARIR DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PEGAWAI PADA DINAS KOMUNIKASI DAN INFORMATIKA STATISTIK KABUPATEN BIMA - Muliati, Muliati; Kusumayadi, Firmansyah (Jurnal Riset Rumpun Ilmu Ekonomi, 2022)
This study aims to determine the effect of partially significant career development on employee job satisfaction at the Department of Communication and Informatics Statistics Bima Regency, to determine the effect of partially significant work motivation on employee job satisfaction at the Department of Communication and Informatics Statistics Bima Regency, to determine the development of career and work motivation simultaneously have a significant effect on employee job satisfaction at the Department of Communication and Informatics Statistics Bima Regency. The instrument in this study used a questionnaire with a Likert scale. The population in this study was 61 employees consisting of 41 civil servants, 7 regional honorary employees, and 13 non-permanent employees at the Department of Communication and Information, Bima Regency. The sample in this study were 41 civil servants with the sampling technique used, namely the purposive sampling technique. Data collection techniques using observation, interviews, questionnaires, documentation. The data analysis technique uses validity test, reliability test, multiple linear regression test, classical assumption test, multiple correlation coefficient test, coefficient of determination, t test and f test with the help of SPSS version 22 for windows. The results showed that career development had no significant effect on employee job satisfaction, work motivation had a significant effect on employee job satisfaction, career development and work motivation had a significant effect on employee job satisfaction at the Department of Communication and Informatics Statistics Bima Regency.